Innovations in Sustainable Construction Materials: A Systematic Evaluation of the Literature on Materials and Production Methods - Feyranda Feyranda (Science and Applied Journal (SIAP), 2024)
Increased awareness of sustainability has driven the construction industry to seek innovation in more environmentally friendly construction materials. This article presents a systematic evaluation of the literature on innovation in sustainable construction materials, with a focus on materials and production methods. Through this approach, we explore current trends, challenges and opportunities in the development of sustainable construction materials. Literature analysis shows the existence of various promising sustainable construction materials, such as bamboo, environmentally friendly concrete, and recycled materials. Additionally, production methods are also an important focus, with the development of advanced technology and more efficient construction practices. These findings have important implications in guiding the future development of the construction industry towards sustainability.